Jembatan Kognitif Etnomatematika Islam: Relevansi Pedagogis Kitab Farā’iḍ al-Ghazāliyya dalam Pembelajaran Modern - Anang Septian; Sofwan Hadi (Civiliza Publishing, Indonesia., 2026)
This research explores the rationality of Islamic inheritance law (Farā’iḍ) through a textual analysis of Kitab Farā’iḍ al-Ghazāliyya by Abdurrahman Muhsin. It addresses the gap in modern studies that often focus on distribution results while overlooking the underlying logical processes. The study aims to describe the mathematical concepts within the text, explain their systematic construction, and examine their relevance to mathematics education. Using a qualitative library research methodology, the study analyzes the primary text to identify its logical structures and reasoning patterns. The results reveal that Kitab Farā’iḍ al-Ghazāliyya incorporates diverse mathematical concepts, including rational numbers, Least Common Multiple (LCM), Greatest Common Divisor (GCD), sets, linear equations, and mathematical logic. These elements are systematically organized to resolve inheritance issues such as aṣl al-mas’ala, sihām, and the mechanisms of ‘awl and radd. The findings confirm the strong logical foundation of Islamic law, positioning this book as a valuable reference for developing integrative mathematics learning models based on Islamic values.